2011
DOI: 10.1007/s13197-011-0258-7
|View full text |Cite
|
Sign up to set email alerts
|

Studies on effect of additives on protein profile, microstructure and quality characteristics of pasta

Abstract: Wheat storage proteins play a vital role in pasta making quality. In the present study, SDS-PAGE, Gel filtration chromatography and Scanning electron microscopy techniques were employed to understand the changes in the wheat protein fractions and their interactions with additives namely Sodium Steroyl Lactate (SSL), Glycerol Monostearate (GMS) and Hydroxy Propyl Methyl Cellulose (HPMC) during processing of pasta. SDS-PAGE studies indicated changes in High Molecular Weight Glutenin (HMW) fractions during drying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Jyotsna et al (2004) also observed finer and stretched protein matrix with the use of GMS at 0.5% level. Similar results of improvement in protein network with the use GMS was also reported by Kim et al (1989) and Purnima et al (2012). According to Krog (1981), SSL forms complexes with starch and protein to form huge aggregates and increases the stability of protein matrix.…”
Section: Scanning Electron Microscope Characteristicssupporting
confidence: 80%
See 1 more Smart Citation
“…Jyotsna et al (2004) also observed finer and stretched protein matrix with the use of GMS at 0.5% level. Similar results of improvement in protein network with the use GMS was also reported by Kim et al (1989) and Purnima et al (2012). According to Krog (1981), SSL forms complexes with starch and protein to form huge aggregates and increases the stability of protein matrix.…”
Section: Scanning Electron Microscope Characteristicssupporting
confidence: 80%
“…() and Purnima et al . (). According to Krog (), SSL forms complexes with starch and protein to form huge aggregates and increases the stability of protein matrix.…”
Section: Resultsmentioning
confidence: 97%
“…When water at high temperatures is used, the noodles do not absorb as much water because HPMC rapidly gels and develops a coating layer (Lee et al, 2010;Purnima and Ramasarma, 2012). This is also accompanied by lower cooking loss, which is a measure of the elution of solid content during cooking.…”
Section: Texture Profile Analysis Of Rice Noodles Containing Hpmcmentioning
confidence: 99%
“…Purnima et al (2012) reported that HPMC forms a network around the starch granules, possibly encapsulating the starch-protein matrix, and, contributing to the lower cooking loss. H-HPMC recorded the lowest water absorption and cooking loss, as it had the highest viscosity among the 3 types of HPMC, thereby forming the most effective coating layer.…”
Section: Texture Profile Analysis Of Rice Noodles Containing Hpmcmentioning
confidence: 99%
See 1 more Smart Citation